Studi Kasus Resiliensi dan Manajemen Kepribadian Santri dalam Meningkatkan Produktivitas di Pondok Pesantren Salafy Miftahus Sholawat - Ratu Darojatun Nisa; Da’i Muhamad Rizkan; Selnistia Hidayani (CV. Lentera Literasi Indonesia, 2026)
This study aims to analyze the role of resilience and student personality management in increasing productivity at the Salafy Miftahus Sholawat Islamic Boarding School. The dense activities of the Islamic boarding school, high discipline, and academic and spiritual demands require students to have good resilience and personality management skills. This study uses a qualitative approach with a case study type. Data were collected through in-depth interviews, observation, and documentation, then analyzed through data reduction, data presentation, and drawing conclusions. The results show that student resilience is reflected in the ability to face the pressures of Islamic boarding school activities, adapt to routines, and maintain emotional stability through social support and religious activities. Student personality management is evident in discipline in managing time, carrying out routines, and responsibility for daily tasks, which in turn has an impact on increasing productivity, both in learning activities and participation in the Islamic boarding school. The conclusion of the study confirms that student productivity is the result of the integration of resilience, personality management, and a conducive Islamic boarding school environment. The implications of this study demonstrate the importance of character strengthening strategies based on Islamic values ​​in improving the quality of self-management and student productivity.